Fabrication and Characterization of Calcium-Phosphate Lipid System for Potential Dental Application - Zhu, Ningxin; Wang, Dan; Xie, Fei; Qin, Man; Lin, Zhiqiang; Wang, Yuanyuan (Frontiers in Chemistry, 2020)
Lipid has been widely studied as a vehicle and loading vector, but there have been no reports of any such related application in the dental field. The purpose of this research was to fabricate and characterize a nano-size calcium-phosphate lipid (CL) system as a potential vehicle in dental regeneration study, wherein the biocompatibility with dental pulp stem cells (DPSCs) was evaluated. The effect of CL on DPSCs proliferation was analyzed by a CCK-8 assay, and the anti-inflammatory effect was investigated by quantitative polymerase chain reaction (qPCR). Moreover, the effect of CL on odontogenic differentiation of inflamed DPSCs (iDPSCs) was studied by Alizarin red staining, tissue-non-specific alkaline phosphatase (TNAP) staining, qPCR, and western blot analyses. The results of this study showed that CL did not affect the proliferation of DPSCs, it down-regulated the inflammatory-associated markers (IL-1β, IL-6, TNF-α, COX-2) of DPSCs treated with Escherichia coli lipopolysaccharide (LPS), and enhanced the in-vitro odontogenic differentiation potential of iDPSCs. This novel biomaterial has a broad application prospect for its bioactivity and flexible physical property, and thus represents a promising pulpal regeneration material.